Guar —A golden crop for arid regions - Kumar, D (Indian Farming, 2015)
Guar is drought hardy summer annual legume of great significance. Low productivity is a cause of great concern. To address related problems efforts have been undertaken to develop need based technologies. Guar varieties maturing in 85-90, 91- 100, 101-110 and 111-120 days with high production potential (1,200- 1,600 kg/ha), high gum content (31- 32%), suited to mechanical harvesting have been developed. Integrated management strategies addressing the infestation by BLB, ALS, PM and RR diseases have been developed. Convenient and economic production technologies have also been developed. Large scale technologies through FLDs have been transferred. Results reveal that grain yield could be harvested up to 2,000-2,200 kg/ha on farmers’ fields. By proper sowing method having desired plant geometry grain yield could be increased by about 37.0%. Weeding is very crucial for the crop up to 25- 30 days. In view of rainfall pattern soil types, productivity level and social factors, technologies have been suggested up to the district level with setting production priorities for each district.